Students’ Interest in Climate Change: Results of a Quantitative Questionnaire-Based Study - Höhnle, Steffen; Velling, Hanna; Schubert, Jan Christoph (Journal of Geography Education, 2023)
Climate change, one of humanity’s main problems, is of particular relevance for geographic education at school. There are hardly any differentiated findings regarding an important learning precondition: students’ interests in climate change. Therefore, students’ interests in climate change were surveyed in a questionnaire-based study in Bavaria. The gathered data were analyzed descriptively and using inferential statistics. Overall, the results show high interest in climate change with remarkable differences regarding interests in different aspects of climate change and between genders and students attending different types of schools.